Entre política e a religião: a defesa sobre o divórcio na Constituinte de 1934 - Mattos, Renan Santos (Horizonte, 2021)
The article aims to analyze the position of Fernando do Ó, lawyer and spiritist, on divorce in the context of intellectual action after the election for the 1934 constituent. Based on the perspective of Pierre Bourdieu and Gilberto Velho, we discuss the thesis entitled "The Divorce", presented in 1934, in which the author articulates the concept of laicity, emancipation of women, and, above all, the notion of family under the legal bias in order to defend the need for revision of Brazilian legislation. Thus, it is questioned how the arguments of the thesis, from Pontes de Miranda and Evaristo de Morais, refer to the construction of law as a science that analyzes the demands of society. inally, it is emphasized that the view on divorce represents a strategy of struggle for the separation between state and religion, for this principle was understood as in opposition to dogmatism and as fundamental for the consolidation of democracy in the Vargas period.